Hábitat productivo de tasajeras (2021)
Analyzing the context of habitability that occurs in the townships of the department of Magdalena, Colombia. It is essential to generate proposals that promote the development of sustainable habitats that improve the quality of life of the communities in these territories. Tasajeras is a village belonging to the municipality of Pueblo viejo, Magdalena. It is a community that lacks quality infrastructure and supply of public and basic services, characterized by subsisting on fishing activity, which is a main determinant of its social, economic and cultural characteristics.